Morphological and lipid metabolism alterations in macrophages exposed to model environmental nanoplastics traced by high-resolution synchrotron techniques - Zingaro, Federica; Gianoncelli, Alessandra; Ceccone, Giacomo; Birarda, Giovanni; Cassano, Domenico; La Spina, Rita; Agostinis, Chiara; Bonanni, Valentina; Ricci, Giuseppe; Pascolo, Lorella (Frontiers in Immunology, 2023)
The release of nano plastics (NPs) in the environment is a significant health concern for long-term exposed humans. Although their usage has certainly revolutionized several application fields, at nanometre size, NPs can easily interact at the cellular level, arising potential harmful effects. M/NPs have a demonstrated impact on mammalian endocrine components, such as the thyroid, adrenal gland, testes, and ovaries, while more investigations on prenatal and post-natal exposure are urgently required. The amount of literature studies on the NPs' presence in biological samples is increasing. However, only a few offer a close study on the model environmental NP-immune system interaction exploited by advanced microscopy techniques. The present study highlights substantial morphological and lipid metabolism alterations in human macrophage M1 exposed to labelled polypropylene and polyvinylchloride nanoparticles (PP-, PVC-NPs) (20 µg/mL). The results are interpreted by advanced microscopy techniques combined with standard laboratory tests and fluorescence microscopy. We report the accurate detection of polymeric nanoparticles doped with cadmium selenide quantum dots (CdSe-QDs NPs) by following the Se (L line) X-ray emission peak at higher sub-cellular resolution, compared to the supportive light fluorescence microscopy. In addition, Scanning Transmission X-ray Microscopy (STXM) imaging successfully revealed morphological changes in NPs-exposed macrophages, providing input for Fourier Transform Infrared (FTIR) spectroscopy analyses, which underlined the chemical modifications in macromolecular components, specifically in lipid response. The present evidence was confirmed by quantifying the lipids droplets (LDs) contents in PP-, PVC-NPs-exposed macrophages (0-100 µg/mL) by the Oil Red O staining. Hence, even at NPs concentrations and incubation time, they do not significantly affect cell viability; they cause an evident lipid metabolisms impairment, a hallmark of phagocytosis and oxidative stress.